Predictors Of Accountability Creating In Educational Accountant: Professionalism As A Mediator - Indah Masri; Thyas Tri Agathya; Ameilia Damayanti; Amelia Oktrivina (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
The Research Examines The Effect Of Accountant Competence, Educator Accountant Commitment, Accountant Ethics And Professionalism As Mediating Variable On Educator Accountantaccountanbility. This Study Took The Objectof Accounting Lecturers In Dkijakarta, Using Data Collectionmethodsthrough Questionnaires. Samplingusingthe Purposive Samplingmethod Withthe Criteria Ofhavingexpertise In The Field Of Accounting Is Realized Through Akt Or Ak Degrees From Several Universitiesin Dkijakarta. The Hypothesis Testing Model Uses Partial Least Square (PLS). Based On The Results Of Data Analysis And Discussion, The Following Research Findings Were Obtained: 1) Accountant Commitmentand Accountant Ethics Have A Positive Effect On Accountability Of Educator Accountants; 2) Accountant Competence, Accountant Commitment And Accountant Ethics Have A Positive Effect On Professionalism;3)Accountant Competence Does Notaffectthe Accountability Of Educator Accountants; 4) Accountantcompetencehasa Positive Effecton Educator Accountability Through Professionalismhas A Fullmediationrole.Theexistence Of Professionalism Is Importantso That It Can Affect The Competence Of Accountantsontheaccountabilityof Educator Accountants; 5) Accountants Commitment And Accountant Ethics Have A Positive Effect On Accountability Accountantthrough Professionalism. Thatis, Professionalism Hasapartialmediationrole. Both The Direct And Indirect Relationship Of Commitmentand Accountantethics Can Encourageeducators To Gain Accountability For Accountants.